Does time spent in the residential neighbourhood moderate the relationship between neighbourhood walkability and transport-related walking? a cross-sectional study from Toronto, Canada. Issue 4 (3rd April 2019) - Chum, Antony; Atkinson, Peter; O'Campo, Patricia
Abstract : Objectives: Studies have investigated the influence of neighbourhood walkability on residents' walking behaviour, aiming to increase physical activity and reduce dependence on automobiles. Previous research, however, has not considered how the amount of time spent in the residential neighbourhood may modify this relationship. Our objective was to determine how time spent in the residential neighbourhood affects the relationship between neighbourhood walkability and walking for transport. Design: Using a cross-sectional sample of 2411 adults, we analysed the association between walkability (an index combining land-use mix, dwelling density and street connectivity) and transport-related walking (controlling for the effects of gender, age, income, self-rated health and regular access to private transport) testing for interactions by time spent in the neighbourhood. Primary outcome measure: Minutes spent walking for transport per week. Setting: Toronto, Canada. Participants: Participants were aged 25 to 65. The survey had a 72% response rate. Results: After adjusting for potential confounders, the walkability index was weakly associated with walking (1 SD of walkability score is associated with 0.25 more minutes walking/week, p<0.01). Land-use mix was more strongly associated with walking than the walkability index. Time spent at the residential neighbourhood modified the relationship between land-use mix and transport-related walking in a dose-effect manner (p<0.01), those spending 5 hours on average at their residential neighbourhood have 0.2 min/day more walking for each additional land-use mix score and those spending 12 hours have 0.5 min/day more walking for each additional land-use mix score. Conclusions: Our findings suggest that walkability is associated with increased walking time, but it is modified by time spent in the neighbourhood. Our study underscores the importance of testing 'time spent in the neighbourhood' as a modifier of environmental exposures in studies of environmental correlates of walking.